Evaluation of Antioxidant Activity in Solanum Ferox (Through DPPH and FRAP Assays) - Karol Giovani Battista Leki; Yahya Febrianto; Yithro Serang (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
The antioxidant properties of natural compounds have garnered significant attention for their potential therapeutic applications. Solanum ferox, a plant traditionally used in several countries for medicinal purposes, has been identified as possessing potential antioxidant properties. However, the extent and efficacy of its antioxidant capacity have not been thoroughly examined, creating a gap in understanding its effectiveness compared to established antioxidants like ascorbic acid. This study aims to evaluate the antioxidant capacity of Solanum ferox using DPPH and FRAP assays across concentrations ranging from 20 to 100 µg/µl, with ascorbic acid serving as a standard reference. The DPPH assay measured the scavenging activity of both samples to assess their radical-quenching properties, while the FRAP assay evaluated their reducing power. Findings indicate that ascorbic acid exhibits significantly higher scavenging activity than Solanum ferox across all concentrations, with consistent activity ranging between 88.4% and 90.88% in the DPPH assay and from 45.16% to 83.89% in the FRAP assay. In contrast, Solanum ferox shows a gradual but much lower increase in activity, from 6.8% to 35.5% in the DPPH assay and from 10.59% to 33.82% in the FRAP assay, suggesting limited antioxidant potential. The study contributes to the understanding of the antioxidant properties of Solanum ferox, highlighting its limited efficacy compared to ascorbic acid and suggesting that further research is needed to explore its potential at higher concentrations or through alternative methods. These insights provide a foundational basis for future studies investigating Solanum ferox as a potential natural antioxidant source.